Ethics and healthcare in the older adult population - Aryan Ayati; Moloud Payab; Zhaleh Shadman; Amirahmad Shojaee; Mojgan Asadi; Farshad Sharifi; Mahbube Ebrahimpur; Bagher Larijani (Journal of Medical Ethics and History of Medicine)
Aging is a natural process involving the loss of several abilities, including cardiovascular, neurologic, musculoskeletal, and social capabilities. In addition to the usual needs, older adults face specific physical and mental challenges. Considering the increase in life expectancy and the large percentage of older adults in most populations, societies should be prepared for the ethical challenges associated with high-demand older generations. A search was conducted across the three main databases: PubMed, Web of Science, and Scopus. Next, 57 qualitative studies were selected to evaluate the ethical concerns and solutions in providing healthcare and treatment for older generations. Two independent researchers screened and assessed the studies, and the results were reported. Our findings showed that the main concern of policymakers and healthcare planners should be observance of principles such as autonomy, dignity, and fair and balanced distribution of medical resources while not prioritizing others over older adults due to their age. The elderly have specific needs, and considering their increasing prevalence and physical and emotional fragility, countries should be prepared to meet their rapidly growing needs.